2018
DOI: 10.2340/00015555-3057
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Treatment Outcome of Oral Tofacitinib with Other Conventional Therapies in Refractory Alopecia Totalis and Universalis: A Retrospective Study

Abstract: Treatment of severe alopecia areata is often challenging and unsatisfactory. However, oral tofacitinib, which is approved for treatment of rheumatoid arthritis, has had promising results. This is the first study to compare the treatment outcomes of tofacitinib with other conventional therapies in patients with refractory severe alopecia areata. After 6 months of treatment, patients on tofacitinib had a higher response rate and greater tolerability than those on topical immunotherapy and oral steroid ± immunosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…Other side effects included gastrointestinal symptoms and mild acne. One patient stopped treatment because of new-onset multiple sclerosis59 [107]Case seriesTofacitinibTofacitinib 5 mg BID PO, increased to 5 mg 3 times daily for 4 unresponsive patients, and then to 10 mg BID for one of theseComparators: oral conventional treatment (steroids + cyclosporine) and diphenylcyclopropenone (DPCP)Systemic/topical2474Efficacy and safetyMedian SALT change: 3rd month: tofacitinib 34.6 (range 0–80), conventional 34.7 (0–89.2), and DPCP 0 (0–53.0) 6th month: tofacitinib 36.5 (0–91.5), conventional 39.9 (0–91.6), and DPCP 0 (0–80)SALT50 3rd month: Tofacitinib: 9 patients (50%), conventional: 7 patients (26.9%), DPCP: 1 patient (3.6%)SALT50 6th month: Tofacitinib: 8 (44.4%), conventional: 9 (37.5%), DPCP: 3 (11.1%)In the tofacitinib group, 6 patients (33.3%) suffered abdominal discomfort and acneiform eruption, most of them mild and transient60 [108]Case seriesTofacitinib5 mg BID POSystemic649Efficacy and safety3/9 patients responded (showing 25–75% regrowth at 6 months)No significant clinical or laboratory adverse events61 [109]Open labelTofacitinib5 mg BID PO, increased to 10 mg BID PO in non-respondersSystemic2412Efficacy8/12 patients ≥ 50% hair regrowth, 3/12 partial < 50% regrowth, and 1 patient no regrowthNA62 [110]Case seriesTofacitinib5 mg BID POSystemic28/364EfficacyPatient #1: progressive hair growth after 9 monthsPatient #2: partial growth of scalp, eyebrow, and axillary hairPatient #3: hair growth on scalp, eyebrows, and skin after 7 monthsPatient #4: complete regrowthNA63 [111]Case reportTofacitinib5 mg BID POSystemic321Efficacy and safetyAlmost complete full body hair regrowthNo adverse effects or laboratory ab...…”
Section: Resultsmentioning
confidence: 99%
“…Other side effects included gastrointestinal symptoms and mild acne. One patient stopped treatment because of new-onset multiple sclerosis59 [107]Case seriesTofacitinibTofacitinib 5 mg BID PO, increased to 5 mg 3 times daily for 4 unresponsive patients, and then to 10 mg BID for one of theseComparators: oral conventional treatment (steroids + cyclosporine) and diphenylcyclopropenone (DPCP)Systemic/topical2474Efficacy and safetyMedian SALT change: 3rd month: tofacitinib 34.6 (range 0–80), conventional 34.7 (0–89.2), and DPCP 0 (0–53.0) 6th month: tofacitinib 36.5 (0–91.5), conventional 39.9 (0–91.6), and DPCP 0 (0–80)SALT50 3rd month: Tofacitinib: 9 patients (50%), conventional: 7 patients (26.9%), DPCP: 1 patient (3.6%)SALT50 6th month: Tofacitinib: 8 (44.4%), conventional: 9 (37.5%), DPCP: 3 (11.1%)In the tofacitinib group, 6 patients (33.3%) suffered abdominal discomfort and acneiform eruption, most of them mild and transient60 [108]Case seriesTofacitinib5 mg BID POSystemic649Efficacy and safety3/9 patients responded (showing 25–75% regrowth at 6 months)No significant clinical or laboratory adverse events61 [109]Open labelTofacitinib5 mg BID PO, increased to 10 mg BID PO in non-respondersSystemic2412Efficacy8/12 patients ≥ 50% hair regrowth, 3/12 partial < 50% regrowth, and 1 patient no regrowthNA62 [110]Case seriesTofacitinib5 mg BID POSystemic28/364EfficacyPatient #1: progressive hair growth after 9 monthsPatient #2: partial growth of scalp, eyebrow, and axillary hairPatient #3: hair growth on scalp, eyebrows, and skin after 7 monthsPatient #4: complete regrowthNA63 [111]Case reportTofacitinib5 mg BID POSystemic321Efficacy and safetyAlmost complete full body hair regrowthNo adverse effects or laboratory ab...…”
Section: Resultsmentioning
confidence: 99%
“…Thus, oral JAK inhibitors can be considered attractive candidates to treat moderate to severe AA. Additionally, tofacitinib was similarly effective but more tolerable in patients with refractory alopecia totalis/universalis (AT/AU) than oral steroids with or without cyclosporin . We thus believe that oral JAK inhibitors may be particularly useful for AA patients who experience treatment failure or cannot tolerate the adverse reactions from other conventional therapies.…”
Section: Case Reportmentioning
confidence: 99%
“…No serious side‐effects of oral JAK inhibitors were noted in the summarized AA studies (Table ), and most of the mild adverse reactions improved during the course of treatment. In patients with latent tuberculosis, tuberculosis reactivation was not observed when isoniazid prophylaxis and tofacitinib were used in combination . However, in patients with poorer overall health, fatal side‐effects have been reported during oral JAK inhibitor therapy.…”
Section: Case Reportmentioning
confidence: 99%
“…18 patients were assigned to the tofacitinib group, 26 patients to the conventional oral treatment group, and 33 to the diphenylcyclopropenone group. In this study, 44.4% of patients in the tofacitinib group, 37.5% in the conventional oral treatment group, and 11.1% in the diphenylcyclopropenone group achieved 50% SALT improvement after 6 months 37 . The group concluded that oral tofacitinib was more effective than topical immunotherapy and more tolerable than the conventional oral treatments.…”
Section: Jak Inhibitorsmentioning
confidence: 59%